The Participation of the Community in Enhancing Education Quality - Hakim, Lukman (CV. Creative Tugu Pena, 2020)
The existence of a school community is very important in order to promote effective education, it aims to mobilize and improve the quality of education in accordance with the needs of the community. The existence of the school communities which represented in the school committee is a basis that is able to make a major contribution to the implementation of learning in schools/madrasas. However, in reality, the function of the school committee in Indonesia, especially in primary schools in NTB, still cannot be carried out to the fullest. This study used a qualitative research approach, a type of case design using a multi-case design. Data collection is done through observation, interviews, and documentation. Data sources were obtained from school principals, teachers, Foundation administrators, parents, and school committees. Data analysis across cases is explanatory. Data analysis starts from a single case and then inter-case analysis. Data were analyzed by checking the data from the form of dominant and less dominant analysis. Checking the validity of the data is done through credibility, transferability, dependability and confirmation. The results of the study shown that; 1) the form of community participation are contributive and consultative. The findings of this study are the development of community participation with basically comprehensive community, the initiative can be define as advisory agency, supporting, controlling and legislator. The concept enables the creation of a superior program and god images of institutions. Keywords: Enhancing Education Quality, Elementary School